Humanitarian Logistics and Its Challenges: The Literature Review - Mat Daud, Mimi Suriani; Muhamad Hussein, Muhamad Zaly Shah; Nasir, Muhamad Emeereza; Abdullah, Rozelin; Kassim, Rahimah; Suliman, Mohd Saipuddin; Saludin, Mohd Rosli (International Journal of Supply Chain Management, 2016)
This study demonstrates the importance of humanitarian logistics as a fields that need an attention by everyone. With the unstable of climate condition, it can be seen that many disaster has happened around the world. The 2011 incidents that strike the develop nation, Japan, has shock the world and teach every country to be better prepared of any unexpected event. The objective of this study is to highlight the challenges in humanitarian logistics process in met the objective relief. Keywords— humanitarian, logistics, challenges,